Motivational telephone intervention to risk gamblers by a state-owned gambling operator in Sweden - Hakansson, Anders; Franklin, Katja; Dahlström, Maria; Lyckberg, Axel (Frontiers in Psychiatry, 2024)
Background and aims: Few studies have tested the effect of a motivational telephone intervention from a gambling operator to clients with high-risk gambling practices. This study aimed to study subsequent limit setting, self-exclusions and gambling post-intervention, compared to controls.Methods: The study assessed a motivational, personalized telephone intervention by the stateowned Swedish gambling operator AB Svenska Spel within its subsection of sports, poker, online casino and bingo gambling. Clients successfully reached with the telephone intervention (n=1,420) were compared to clients who could not be reached (n=1,504).Gambling practices during eight weeks pre-intervention were assessed, and outcome measures limit setting, self-exclusion, and gambling four weeks post-intervention.Results: The telephone intervention was associated with increased limit settings (10 vs 5 percent, p<.001), self-exclusions (11 vs 8 percent, p<.01), lowered theoretical losses (p<0.001), but not significantly associated with gambling abstinence (18 vs 15 percent, p=.07). In unadjusted analyses of sub-groups, significant associations of the intervention with full gambling abstinence were seen in people who gamble on online casino/bingo (19 vs 14 percent, p<.01), but not in sports bettors. In logistic regression, the intervention was not with full week 1-4 abstinence.A personalized motivational telephone intervention to people displaying highrisk gambling, delivered by a gambling operator, is promising, and effects were seen on the uptake of responsible gambling tools post-intervention. Effects may be more pronounced in users of chance-based, online games, than in sports bettors.